Typology of Old Houses in Kampung Arab Tanjung Selor, North Kalimantan - Nur Asriatul Kholifah; Anisah Azizah; Putri Nopianti; Pandu K. Utomo; Kartika Tristanto; Ratri Bodromulatsih (Malikussaleh University, Aceh, Indonesia, 2026)
This study examines the typology of old houses in Kampung Arab Tanjung Selor, Bulungan Regency, North Kalimantan, a historic Arab settlement dating back to the 19th century. This settlement has historical value and unique old buildings, whose condition is deteriorating due to rapid development, requiring preservation efforts. Therefore, this study aims to identify and classify the typology of old residential buildings in Kampung Arab to support its development as a cultural heritage area. The method used is a qualitative descriptive, typological approach, in which data are collected through field observations, interviews with community leaders and elders, and documentation. The objects of study were three old houses believed by local community leaders to have been built during the arrival of the Arabs in Tanjung Selor, namely the houses of Salim bin Djoemaan, Umair Al Hasyim, and H. Muhamad Bansir, all of which are more than 100 years old and still retain their original structures. The results of the study show that these old houses share architectural similarities with Malay architecture and adopt the stilted structure of Kalimantan vernacular architecture as an adaptation to the swampy environment. The house's floor plan is rectangular, symmetrical, and clearly divided into public zones (veranda, living room), private zones (family room, bedrooms, dining room), and service zones (kitchen, bathroom). The separation of these spaces demonstrates the high value placed on privacy. Overall, these old houses embody Islamic values such as efficiency, egalitarianism, privacy, and local wisdom.